Transcription factors AP-2α and AP-2β regulate distinct segments of the distal nephron in the mammalian kidney - Joseph O. Lamontagne; Hui Zhang; Alia M. Zeid; Karin Strittmatter; Alicia D. Rocha; Trevor Williams; Sheryl Zhang; Alexander G. Marneros (Nature Communications, 2022)
How the distal nephron is patterned during kidney development has been difficult to study. Here they show that AP-2β is required for the formation and postnatal function of distal convoluted tubules, whereas AP-2α has a role in maintaining the structure of medullary collecting ducts.